Taxonomic Revision and Conservation Review of Sinocyclocheilus grahami (Regan, 1904), the Only Known Cavefish Applied Both in the Traditional Medicine and Aquaculture - Wuyang Liu; Yahui Zhao; Jinqing Huang (Fishes)
Sinocyclocheilus grahami (Regan, 1904) is the only known cavefish used both in traditional medicine and aquaculture in the world, and it is also a national protected animal. However, its taxonomy and distribution remain ambiguous, hindering effective conservation and resource utilization. This study clarifies the taxonomy of S. grahami through field surveys, specimen examination, and literature reviews, combined with principal component analysis (PCA) for morphological comparison. The results indicate that S. grahami and S. guanduensis show no significant morphological differences, supporting the recognition of S. guanduensis as a junior synonym of S. grahami. Sinocyclocheilus huanglongdongensis, and S. hei, once synonyms of S. grahami, should be valid. The species faces a significant population decline, and its distribution is now restricted to a few unpolluted streams around Dianchi Lake. While artificial breeding has been successful, further studies are needed to determine the medicinal efficacy of these individuals. To address the conservation and sustainable use of this species, habitat restoration should be prioritized, particularly in protecting cave environments and maintaining groundwater connectivity. Additionally, artificial breeding and release in restored habitats are essential to establish a sustainable ecological governance system that supports biodiversity and regional development.